Nicotinic acetylcholine receptors and learning and memory deficits in Neuroinflammatory diseases - Echeverria, Valentina; Mendoza, Cristhian; Iarkov, Alex (Frontiers in Neuroscience, 2023)
Animal survival depends on cognitive abilities such as learning and memory to adapt to environmental changes. Memory functions require an enhanced activity and connectivity of a particular arrangement of engram neurons, supported by the concerted action of neurons, glia, and vascular cells. The deterioration of the cholinergic system is a common occurrence in several neurological disorders exacerbated by aging, such as traumatic brain injury (TBI), Posttraumatic stress disorder (PTSD), Alzheimer's disease (AD), and Parkinson's disease (PD). Cotinine is a drug with neuroprotector, antidepressant, anti-inflammatory, antioxidant, and memory enhancing effects[1]. Current evidence suggests that its beneficial effects on cognition results from the positive modulation of the α7-nicotinic acetylcholine receptors (nAChRs) and the inhibition of the toll like receptors (TLRs)[2]. The nAChRs affect brain functions by modulating neurons, glia, endothelial cells, immune cells, and dendritic cells and controlling inhibitory and excitatory neurotransmission through the GABA interneurons. In addition, the positive modulation of the α7nAChRs by Cotinine reduced neuroinflammation and the release of pro-inflammatory cytokines by immune cells. Also, α7nAChRs stimulate signaling pathways supporting the structural, biochemical, electrochemical, and cellular changes during the cognitive processes, including Neurogenesis. Here, potential mechanisms of action of Cotinine on memory preservation in aging and neurological diseases are discussed. Keywords: nicotinic acetylcholine receptors, learning and memory, aging, Cotinine, Neurogenesis, Posttraumatic stress disorder, traumatic brain injury